2018
DOI: 10.1080/14787210.2018.1441025
|View full text |Cite
|
Sign up to set email alerts
|

Latent tuberculosis in childhood: tolerability of two different therapeutic approaches

Abstract: Both regimens resulted safe. Hepatotoxicity occurred rarely and within the first month. For this reason, it may be appropriate to perform liver function tests after about one month from the beginning of therapy to avoid diagnostic delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other adverse events were mostly observed in isolated cases. The association between anti-TB drugs and hepatotoxicity is known and has been analysed in numerous studies [37,38], but the fact that few children experienced it is consistent with Tersigni et al, who observed a lower incidence rate of hypertransaminasemia in the paediatric population [39] compared to the incidence rate in the general population [38]. Although the majority of studies associate second-line drugs with adverse events [40,41], only one second-line drug was suspended due to acute kidney injury, suggesting that second-line drugs were well tolerated by the children in the study.…”
Section: Discussionmentioning
confidence: 52%
“…Other adverse events were mostly observed in isolated cases. The association between anti-TB drugs and hepatotoxicity is known and has been analysed in numerous studies [37,38], but the fact that few children experienced it is consistent with Tersigni et al, who observed a lower incidence rate of hypertransaminasemia in the paediatric population [39] compared to the incidence rate in the general population [38]. Although the majority of studies associate second-line drugs with adverse events [40,41], only one second-line drug was suspended due to acute kidney injury, suggesting that second-line drugs were well tolerated by the children in the study.…”
Section: Discussionmentioning
confidence: 52%
“…Prophylactic and preventive treatment is usually welltolerated [15] and has been shown to be very effective [8,9]. However, evidence from high-incidence settings shows multifactorial barriers to successful implementation including factors concerning screening and adherence, healthcare provider acceptability, and fear of isoniazid resistance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatotoxicity is a well-known adverse effect of INH and RMP. The administered dose, TB disease severity, and being an "INH slow-acetylator" have been identified as risk factors for INH-or RIF-associated hepatotoxicity [40,41]. However, a very low incidence of adverse events and an increased compliance with the shorter combination therapy compared to 9-months INH has been clearly demonstrated in children [42,43].…”
Section: Plos Onementioning
confidence: 99%